2014
DOI: 10.1177/0731948714555020
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Regression Discontinuity and Multivariate Analyses of Variance

Abstract: The purpose of this study was to compare the results of a regression discontinuity design (RDD) with those of an experimental design of a tiered vocabulary intervention for children at risk for reading disability to determine RDD’s feasibility as a research methodology for this type of study. Researchers reanalyzed an archival dataset of a previous study that determined the effectiveness of the intervention through a randomized experiment. Results were comparable for the receptive outcome scores in direction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Although previous studies have evaluated the impact of Tier-2 interventions using an RD design (e.g., Baker, Smolkowski, Chaparro, Smith, & Fien, 2015; Bryant, Bryant, Gersten, Scammacca, & Chavez, 2008; Bryant, Bryant, Gersten, Scammacca, Funk, et al, 2008), we found no previous studies using this design to evaluate the impact of a Tier-1 instruction to improve the mathematical performance for students with a wide range of mathematical proficiencies. RD designs have commonly been used to evaluate the effects of Tier-2 interventions when all students with special needs receive treatments, and the RD approach is used to detect effects of intervention even without the use of a control group (Ashworth & Pullen, 2015). In addition, studies have used student scores on specific measures as the cutoff to determine which students were at risk for academic failure and needed an additional tier of instruction or whether a more intensive secondary tier (received Tier 1 and Tier 2) would improve academic outcomes more so for students who received only Tier 1 (Baker et al, 2015).…”
Section: Study Context and Rationale For A Regression Discontinuity Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have evaluated the impact of Tier-2 interventions using an RD design (e.g., Baker, Smolkowski, Chaparro, Smith, & Fien, 2015; Bryant, Bryant, Gersten, Scammacca, & Chavez, 2008; Bryant, Bryant, Gersten, Scammacca, Funk, et al, 2008), we found no previous studies using this design to evaluate the impact of a Tier-1 instruction to improve the mathematical performance for students with a wide range of mathematical proficiencies. RD designs have commonly been used to evaluate the effects of Tier-2 interventions when all students with special needs receive treatments, and the RD approach is used to detect effects of intervention even without the use of a control group (Ashworth & Pullen, 2015). In addition, studies have used student scores on specific measures as the cutoff to determine which students were at risk for academic failure and needed an additional tier of instruction or whether a more intensive secondary tier (received Tier 1 and Tier 2) would improve academic outcomes more so for students who received only Tier 1 (Baker et al, 2015).…”
Section: Study Context and Rationale For A Regression Discontinuity Designmentioning
confidence: 99%
“…The performance of these students was compared to similar students who received business-as-usual instruction. RD designs are quasi-experimental and permit strong causal inferences like those associated with randomized controlled trials for research in tiered instruction (Ashworth & Pullen, 2015; Lee & Lemieux, 2010). In special education, RD designs are appropriate in studying the effectiveness of interventions such as with MTSS studies when using a cutoff so that “the treatment effect observed visually around a cut-off value can also be extended in both directions from the cut-off value” (Ryoo & Pullen, 2017, p. 138).…”
mentioning
confidence: 99%
“…Okuduğunu anlamanın gerçekleşmesi için okuyucunun metindeki sözcükleri ve cümleleri anlaması ve bunları metnin geri kalanı ve kendi var olan bilgileri ile ilişkilendirmesi gerekmektedir (Lai, George, Benjamin, Schwanenflugel, & Kuhn, 2014;Sarı, 2015). Bu durum ise okuyucunun sözel dil becerileri ve sözcük bilgileri ile yakından ilişkilidir (Ashworth & Pullen, 2014;Cronin, 2014;Jalongo & Sobolak, 2011;Lowder, Choi, & Gordon, 2013;Prior, Goldina, Shany, Geva, & Katzir, 2014;Quinn, Wagner, Petscher, & Lopez, 2015;Shing, 2013). Çok sayıda çalışmada alıcı ve ifade edici dil becerileri yüksek olan çocukların okuduğunu anlamada daha başarılı oldukları bulunmuştur (Catts, Adlof, & Weismer, 2006;Dickinson & Tabors, 2001;Muter, Hulme, Snowling, & Stevenson, 2004;National Early Literacy Panel, 2008;Storch & Whitehurst, 2002).…”
Section: Sonuç Ve Tartışmaunclassified